The share of women in decision-making positions across different levels of government - Espírito-Santo, A.; Santos, M. H. (Representation, 2021)
This paper investigates formal and informal patterns of the recruitment process and the features of types of elections to shed light on what affects the share of women across levels of government (European, national, and local). A single country and party – the Portuguese Socialist Party – was analysed to rule out intervening factors, and 19 in-depth interviews were conducted. Our findings highlight the specificities of each type of election, their interactions with the recruitment process, and the relevance of informal factors.